A Perovskite Electrolyte That Is Stable in Moist Air for Lithium‐Ion Batteries. (7th June 2018) - Li, Yutao; Xu, Henghui; Chien, Po‐Hsiu; Wu, Nan; Xin, Sen; Xue, Leigang; Park, Kyusung; Hu, Yan‐Yan; Goodenough, John B.
Abstract: Solid‐oxide Li + electrolytes of a rechargeable cell are generally sensitive to moisture in the air as H + exchanges for the mobile Li + of the electrolyte and forms insulating surface phases at the electrolyte interfaces and in the grain boundaries of a polycrystalline membrane. These surface phases dominate the total interfacial resistance of a conventional rechargeable cell with a solid–electrolyte separator. We report a new perovskite Li + solid electrolyte, Li0.38 Sr0.44 Ta0.7 Hf0.3 O2.95 F0.05, with a lithium‐ion conductivity of σ Li =4.8×10 −4  S cm −1 at 25 °C that does not react with water having 3≤pH≤14. The solid electrolyte with a thin Li + ‐conducting polymer on its surface to prevent reduction of Ta 5+ is wet by metallic lithium and provides low‐impedance dendrite‐free plating/stripping of a lithium anode. It is also stable upon contact with a composite polymer cathode. With this solid electrolyte, we demonstrate excellent cycling performance of an all‐solid‐state Li/LiFePO4 cell, a Li‐S cell with a polymer‐gel cathode, and a supercapacitor. Abstract : Die Verwendung eines Perowskits, das in Wasser bei pH‐Werten zwischen 3 und 14 stabil ist, in einer Festkörper‐Li/LiFePO4 ‐Zelle, einer Li‐S‐Zelle oder einem Superkondensator führt zu einem niedrigen Übergangswiderstand und exzellenter Zyklierbarkeit.